The rupture process of the Hualien M7.3 sequence on April 3, 2024 - Zhigao Yang; Huifang Chen (Earthquake Research Advances)
The Hualien M 7.3 earthquake on April 3, 2024, was a significant and strong earthquake in Taiwan, China in the past two decades. The rupture process of the main shock and strong aftershocks is of great significance to the subsequent seismic activity and seismogenic tectonic research. Based on local strong-motion data, we used the IDS (Iterative Deconvolution and Stacking) method to obtain the rupture process of the mainshock and two strong aftershocks on the 23rd. The rupture of the mainshock was mainly unilateral, lasting 31 ​s, with a maximum slip of 2 ​m, and the depth of the large slip zone is about 41–49 ​km. There is a clear difference between the rupture depth of the main shock and the two strong aftershocks. The depths of the large slip zones of the latter two are 3–9 ​km and 8–10 ​km, respectively. There is also a significant difference in the seismogenic fault between the mainshock and the aftershocks, and we believe that there are two seismogenic fault zones in the study area, the deep and the shallow fault zone. The slip of the deep faults activates the shallow faults.